Portrait Resilience of Victims of Violence Sexual in the Novel Perempuan yang Menangis Kepada Bulan Hitam - Prabaningrum, Dyah; Pristiwati, Rahayu; PYU, Asep; Tyaskyesti, Swarinda (Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
Throughout 2021-2024, cases of sexual violence against women have increased. The impact of violence on victims tends to be traumatic. Trauma can hinder selfdevelopment, so it needs to be overcome either by the individual's own efforts or professional assistance to have the ability to recover (resilience). Efforts to prevent sexual violence and handle post-violence victims can use literary education alternatives. Literary works can affect the inner psychology of humans. This will encourage humans as connoisseurs of literary works to be motivated to imitate something contained in them. The novel The Crying Woman To Bulan Hitam is one of the literary works that tells the true story of a woman victim of sexual violence who can find resilience. The study of this novel uses the hermeneutic method to analyze the data. This research is expected to provide a discourse on the resilience of victims of sexual violence. The results obtained from this study are that the novel Perempuan who Cried on the Black Moon neatly describes the process towards resilience, which is represented by the character Magi Diela, which includes two factors, namely I have and I am.